Acoustic emission characteristics of ϕ480 mm composite shell with structure and heat protection integration during water pressure test - HUI Xuemei; ZHANG Gang; HOU Xiao; CUI Hong; ZHANG Chengshuang; BAO Yanling (Journal of Aeronautical Materials, 2022)
In order to meet the high requirements of future high-speed and high acceleration tactical missiles for shell bearing capacity and heat protection function, the integrated structure-heat protection ϕ480 mm composite shell was prepared by dry winding process, in which the structure layer adopted T700 carbon fiber/cyanate ester composite, and the heat protection layer adopted composite heat protection structure. The internal pressure, acoustic emission and hydraulic burst tests had been done for integrated structure-heat protection ϕ480 mm shell. The strain variation law, the damage type and damage location of ϕ480 mm composite shell were researched. The structural integrity of external heat protection materials was evaluated. The capacity of bearing internal pressure load was also assessed for the integrated structure-heat protection ϕ480 mm composite shell. The results show that the strain of ϕ480 mm composite shell is linear with the pressure and increased with the raising pressure. The acoustic emission signals, such as resin cracking, monofilament fracture, fiber bundle fracture and delamination are distributed in the dome areas under the internal pressure. The Felicity ratio of ϕ480 mm composite shell is 0.96 after secondary loading. The bursting pressure of ϕ480 mm composite shell is 18.6 MPa, and the vessel characteristic coefficient reaches 42.1 km. The fiber fracture occurs in the dome areas. A small amount of fiber fuzzing, broken wire and whitening appear on the surface of the heat resistant layer material, and no delamination and shedding occur, maintaining good structural integrity.